(untitled) (Journal of the College of Basic Education, 2022)
The dramatic structure of the hero’s personality in the children’s theater performances must meet the conditions for conveying the meaning and the idea in a simple way and far from ambiguity and complexity in order to reach the recipient with ease. Therefore, the director in the children’s theater is responsible for communicating the idea of ​​the play and convincing the recipient (the child) of the idea of ​​the work in order to select The best methods for developing the educational process, and they find this educational medium an encouraging outlet for what they aspire to, because it has good educational, artistic and educational characteristics. Therefore, the research problem can be summed up in the following question